FAKTOR-FAKTOR PENENTU PERENCANAAN PEMBANGUNAN DESA DI DISTRIK AYAMARU UTARA KABUPATEN MAYBRAT PROVINSI PAPUA BARAT - Arne, Yunita; Pangkey, Masje Silija; Lengkong, Florence Daicy (Sam Ratulangi University, 2016)
ABSTRACT: This study originated from the initial observation in several villages in the area ofthe District of North Ayamaru Maybrat Regency, West Papua Province showed that the success rate ofrural development in this region is still very low terkategori, where most people categorized poor orunderprivileged families. This indication shows that the implementation of rural development has notbeen based on an effective rural development planning. Thus, this study aims to (1) To determine theeffectiveness of rural development planning; (2) To analyze whether the factor of leadership andcultural values also determine the effectiveness of rural development planning; and (3) To measure thesize of the contribution factor of leadership and cultural value to the effectiveness of rural developmentplanning in the District of North Ayamaru Maybrat Regency, West Papua Province.The design used inthis research is the design of diagnostic analytic, by applying descriptive-quantitative method. Samplesdrawn by purposive sampling of respondents as many as 36 employees / service personnel, then spreadQuestionnaire (a questionnaire) and the results are analyzed by applying descriptive statistical analysistechniques and partial regression analysis and multiple regression as well as product momentcorrelation and multiple correlation.The research results presented as follows: (1) The average achievements of the effectiveness ofrural development planning in the District of North Ayamaru Maybrat district is in the category of